HTC212: Basic Eastern Cookery / Faculty of Hotel & Tourism Management - UiTM, Faculty of Hotel and Tourism Management (2023)
The course provides the fundamental concepts, skills, and techniques of basic eastern cooking. The students will be given the hands-on experience on how to prepare products derivatives with different types of cooking technique. This subject will gather such influences whereby the students will undergo pre-preparation, preparation, cooking and plating food items from major ethnic groups in Malaysia.